Design, synthesis, and evaluation of novel coumarin-dithiocarbamate derivatives (IDs) as anti-colorectal cancer agents - Heping Zhu; Shilong Ying; Bingluo Zhou; Xinyang Hu; Xiao Liang; Wangyu Li; Dungai Wang; Hongchuan Jin; Yuanjiang Pan (Taylor & Francis Group, 2021)
Colorectal cancer (CRC) is a common malignant tumour of human digestive tract. The high mortality rate of CRC is closely related to the limitations of existing treatments. Thus, there is an urgent need to search for new anti-CRC agents. In this work, twenty novel coumarin-dithiocarbamate derivatives (IDs) were designed, synthesized and evaluated in vitro. The results suggest that the most active compound ID-11 effectively inhibited the proliferation of CRC cell lines while shown little impact on normal colon epithelial cells. Mechanism studies revealed that ID-11 displayed bromodomain-containing protein 4 inhibitory activity, and induced G2/M phase arrest, apoptosis as well as decreased the expression levels of the key genes such as c-Myc and Bcl-2 in CRC cell lines. Moreover, the ADMET properties prediction results shown that ID-11 possess well metabolic characteristics without obvious toxicities. Our data demonstrated that compound ID-11 may be a promising anti-CRC agent and deserved for further development.